2014
DOI: 10.1186/1472-6947-14-73
|View full text |Cite
|
Sign up to set email alerts
|

Measuring decision quality: psychometric evaluation of a new instrument for breast cancer chemotherapy

Abstract: BackgroundWomen diagnosed with early stage (I or II) breast cancer face a highly challenging decision – whether or not to undergo adjuvant chemotherapy. We developed a decision quality instrument for chemotherapy for early stage breast cancer and sought to evaluate its performance.MethodsCross-sectional, mailed survey of recent breast cancer survivors, providers, and healthy controls and a retest survey of survivors. The decision quality instrument includes questions on knowledge and personal goals. It results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…1416 Patients also have incomplete knowledge about systemic therapy, with frequent overestimation of the survival benefit of chemotherapy. 17, 18 Our participants were more educated than the average population of women undergoing mastectomy for breast cancer, and could all read or speak English. Given the demographics of our study population, we expect that knowledge about reconstruction in the breast cancer population at large may be even lower than what we found here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1416 Patients also have incomplete knowledge about systemic therapy, with frequent overestimation of the survival benefit of chemotherapy. 17, 18 Our participants were more educated than the average population of women undergoing mastectomy for breast cancer, and could all read or speak English. Given the demographics of our study population, we expect that knowledge about reconstruction in the breast cancer population at large may be even lower than what we found here.…”
Section: Discussionmentioning
confidence: 99%
“…10 Further details of the DQI development and validation process have been described before. 1012 The DQI covers three broad domains.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies examining knowledge retention and decision making among patients with breast cancer have concentrated on surgery (mastectomy vs breast‐conserving surgery) or systematic treatments . The results indicated that patients with breast cancer often overestimate treatment benefits .…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] The results indicated that patients with breast cancer often overestimate treatment benefits. 9,10 For instance, less than one-third of women with breast cancer correctly reported expected mortality from breast cancer without chemotherapy or hormonal therapy; most patients who answered incorrectly overestimated the benefit of chemotherapy. 9 Similarly, only slightly more than half of patients correctly reported no survival difference between breastconserving surgery vs mastectomy within 24 hours of surgical consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation